Implementasi pembiayaan mudharabah dalam meningkatkan kesejahteraan anggota koperasi pp. Islamiyah syafi’iyah - Deny Zainur Rizqi; Mohammad Syaiful Su'ib (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze the implementation of mudharabah financing at the Islamiyah Syafiiyah Islamic Boarding School Cooperative and its contribution to members’ well-being in a comprehensive manner, covering economic, social, and business sustainability aspects. Additionally, this study also examines the role of Sharia contract literacy and the effectiveness of business mentoring in supporting the success of the financing. The method used is a qualitative approach with a descriptive-analytical character. The research findings indicate that mudharabah financing has been conducted in accordance with Sharia principles and has contributed to improving members’ welfare, particularly in the economic aspect through increased income and business development. However, its effectiveness has not yet been optimal due to factors such as members’ contract literacy levels, the quality of business mentoring, and an unstructured monitoring system. The implications of this study emphasize the importance of improving contractual literacy, strengthening business mentoring, and improving the cooperative management system to optimize the role of mudharabah financing in a sustainable manner.).